A Coherent Minimum-Process Dependable Reclamation Line Collation Scheme for Fault-Tolerant Mobile Distributed Systems - Deepak Dagar, Ajay Sharma, Sanjeev Kumar, Ajeet Kumar, Mohit Kumar (Mathematical Statistician and Engineering Applications, 2023)
We advocate a minimal-process coordinated Dependable Reclamation Line Collation arrangement for non-deterministic mobile distributed interconnection; where no incompetent recuperation-points are captured. An effort has been made to moderate the intrusion of proceedings and synchronization overhead. We capture the partial transitive interdependencies during the normal accomplishment by piggybacking interdependency arrays onto computation communications.Recurrent terminations of Dependable Reclamation Line Collation arrangement may happen in mobile interconnection due to exhausted battery, non-voluntary disengagements of M_Nodules (Mobile Nodules), or poor mobile connectivity.Therefore, we advocate that in the first stage, all pertinent M_Nodules will capture evanescent recuperation-point only. Evanescent recuperation-point is stored on the memory of M_Nodule only. In this case, if some proceeding miscarries to capture recuperation-point in the first stage, then M_Nodules need to abandon their evanescent recuperation-points only. In this way, we try to moderate the loss of Dependable Reclamation Line Collation (DRL-collation) work when any proceeding miscarries to capture its recuperation-point in coordination with others